Indonesian Cyber Law Formulation in The Development of National Laws In 4.0 Era - Nur Azmi, Rama Halim (Universitas Negeri Semarang, 2020)
The digital age has made the loss of boundaries for interaction and communication which then creates a new world of cyberspace. The cyberspace entity on the one hand provides advantages and on the other hand, also causes losses if there is no protection in cyberspace. The protection of cyberspace in Indonesia is still far from good and tends to be bad. Even President Susilo Bambang Yudhoyono has been a victim of the weak protection of cyberspace. These weaknesses are the implications of the existence of norms that are legal norms which are the basis of the implementation of cyberspace protection in Indonesia. In this paper, we will discuss the problems of cyberspace in Indonesia and how legal norms should be present as a means of social control and engineering.Especially cyberspace in order to realize order and security in cyberspace. The method used in this study is the normative juridical method with the legislation approach and case approach.